1990
DOI: 10.1002/ajim.4700180104
|View full text |Cite
|
Sign up to set email alerts
|

Carbon disulfide exposure and neurotoxic sequelae among viscose rayon workers

Abstract: In Norway's only viscose rayon plant, carbon disulfide (CS2) concentrations in ambient air usually were between 30 and 50 mg/m3 during the first 23 years of production. From 1970/1971 until the factory was closed in 1982, corresponding values were 10-25 mg/m3. Through all of these years, high peak exposures of CS2 and H2S occurred. In 1986, 16 of the 24 men still at work in 1982 and with at least 10 years' experience in the spinning room agreed to participate in this study. Clinical neurological examination de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 16 publications
2
25
1
1
Order By: Relevance
“…An investigation in a viscose rayon plant in Norway, where concentrations of CS 2 were below 30 mg/ m 3 but with peak exposures of CS 2 , showed that 4 yr after the cessation of exposure in 14 out of 16 workers toxic encephalopathy was diagnosed 17) . Most frequent symptoms were memory impairment, irritability, tiredness, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation in a viscose rayon plant in Norway, where concentrations of CS 2 were below 30 mg/ m 3 but with peak exposures of CS 2 , showed that 4 yr after the cessation of exposure in 14 out of 16 workers toxic encephalopathy was diagnosed 17) . Most frequent symptoms were memory impairment, irritability, tiredness, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Karai et al 6) concluded that microaneurysm and pigmentary epithelium atrophy or degeneration is early signs of chronic CS 2 exposure, revealing a consistent dose-response relationship with the duration of CS 2 exposure within the same age strata. Vascular effects of CS 2 , particularly vascular encephalopathy has been described by Italian and Japanese researchers [7][8][9] . The brain MRI positive for vascular encephalopathy showed a strong correlation with CS 2 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The information to be collected was determined by a series of working group meetings based on published references [2][3][4][5][6][7][8][9][10] and the pilot study on the study subjects. The major area or mean of the data collection consisted of three parts: 1) Interview of all subjects to collect relevant information such as CS 2 exposure, past medical history including drug use, presence of 45 selected symptoms within the last month, Minnesota Multiphasic Personality Inventory (MMPI) and others.…”
Section: Data Collectionmentioning
confidence: 99%
“…(52)(53)(54)(55)(56). Enfin, un grand nombre de processus industriels mettent enjeu l'hydrogène sulfuré, soit comme matière première (57), soit comme produit secondaire ou déchet de fabrication (52,(58)(59)(60)(60)(61). Le dosage des ions sulfures est généralement réalisé par ionométrie (60).…”
Section: L'hydrogène Sulfuréunclassified